The results of using lean technologies in assessing the cardiovascular risk based on ultrasound markers of atherosclerosis - E. I. Tsukanova; S. S. Aleksanin (Российский кардиологический журнал)
Aim. To establish the practical value of studying ultrasound markers of atherosclerosis for assessing cardiovascular risk as a part of screening of the population based on lean technologies.Material and methods. The study included 305 patients. The age of participants ranged from 31 to 84 years, the median age was 61,0 years. The object of study was 1830 extracranial vessels, including common carotid arteries, internal carotid arteries, subclavian arteries. Duplex ultrasound was using an Acuson 2000 ultrasound system with a frequency of 3-9 MHz. An abbreviated ultrasound protocol was used. The obtained data were processed using the software package Statistica 12.0 (StatSoft, USA).Results. As a result of lean technology application, the duration of procedure was significantly reduced, and the process was improved by 6 times. Changes in intimamedia thickness (IMT) were detected in 42,6% of cases, and significantly more changes in IMT were found in women (48,1%) than in men (25,0%), p=0,0005. Atherosclerotic plaques (ASP) were detected in 53,4% of cases (men — 68,1%; women — 48,9%), p=0,0043. In men <50 years of age, a more intense increase in ASP prevalence than in women was recorded. Starting from 50 years old, ASP prevalence has leveled off. The prevalence of carotid atherosclerosis at any age was higher in men. From the age of 50, sex differences had no significance, p=0,133. In 87,1% of cases, ASP was located within the bifurcation. In the studied groups, obstruction to 50% were more common (46,2%, p=0,0005). Questioning revealed that over the past three years, duplex ultrasound was performed in 21% of patients. Satisfaction with the quality of the procedure was 57,0% (174/305).Conclusion. The results of the study indicate the high practical value of ultrasonic markers of atherosclerosis using abbreviated ultrasound protocol as a part of screening of the population. The inclusion of noninvasive vascular imaging data in screening programs will help to achieve targets for reducing cardiovascular mortality and personalize the assessment of cardiovascular risk.